Retinal small vessel narrowing in women with gestational diabetes, pregnancy-associated hypertension, or small-for-gestational age babies - Phillipos, Joseph; Luong, Thao Vi; Chang, Deborah; Varadarajan, Suresh; Howat, Paul; Hodgson, Lauren; Colville, Deb; Savige, Judy (Frontiers in Medicine, 2023)
Background: Gestational diabetes, pregnancy-associated hypertension and small-for-gestational age babies all impair placental vascularisation. This study compared the effects of these conditions on systemic small vessel calibre in the retina.Methods: This was a cross-sectional observational study of consecutive pregnant women recruited from an antenatal clinic. Participants underwent a Glucose Tolerance Test, BP measurements, and were examined for small-for-gestational age babies as per national guidelines. They also underwent retinal photography with a non-mydriatic camera, and vessel calibres were measured with a validated semi-quantitative system at a retinal grading centre. Some participants also underwent testing of retinal vascular responsiveness to a flickering light.Results: Women with gestational diabetes (n=68) had a higher mean arterial pressure (85 + 9 mm Hg) than normal pregnant women (n=27, 80 + 8 mmHg, p=0.01). They also had smaller mean retinal arteriole (147.5 ± 13.6 μm and 159.7 ± 6.7 μm respectively, p<0.01) and venular calibre (221.0 ± 13.4 μm and 232.8 ± 20.1 μm respectively, p<0.01) than normal. However their babies' mean birth weights were not different from normal (3,311 ± 558 g and 3,401 ± 600 g respectively, p=0.48). They also demonstrated a trend to reduced retinal arteriolar dilatation (3.5 ± 1.3%, n=23) in response to vasodilatory stimuli (4.4 + 1.8%) (n=11) (p=0.08) consistent with endothelial dysfunction.Women with pregnancy-associated hypertension (n=35) had a higher mean arterial pressure (101 ± 12 mm Hg, p<0.01), a smaller mean retinal arteriolar calibre (139.9 ± 10.6 μm, p<0.0001), and a lower baby mean birth weight than for normal pregnancies (3,095 ± 443g, p=0.02).Likewise, women with small for gestational age babies (n=31) had a higher mean arterial pressure (89 ± 19 mm Hg, p=0.03), a smaller mean retinal arteriolar calibre (141.6 ± 12.8 μm, p<0.01) and a lower baby mean birth weight than for normal pregnancies (2,468 ± 324g, p<0.0001) Conclusion: Mean retinal arterial calibre was reduced in women with gestational diabetes, pregnancy-associated hypertension or small-for-gestational age babies. The reduction in calibre was greatest in pregnancy-associated hypertension and small-for-gestational age babies. Systemic arteriole narrowing may contribute to the pathogenesis of placental vascular dysfunction in these conditions.